2003
DOI: 10.1364/ol.28.000974
|View full text |Cite
|
Sign up to set email alerts
|

Track of a fiber fuse: a Rayleigh instability in optical waveguides

Abstract: The phenomenon colloquially known as a fiber fuse occurs when an optical fiber carrying high power is damaged or in some way abused. Beginning at the damage site a brilliant, highly visible plasmalike disturbance propagates back toward the optical source at speeds ranging from 0.3 to approximately 3 m/s, leaving in its wake a trail of bubbles and voids. We suggest that the bubble tracks in fused fibers are the result of a classic Rayleigh instability that is due to capillary effects in the molten silica that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 8 publications
4
29
0
Order By: Relevance
“…13). This modulation may suggest the instability of the plasma or the surrounding melt as proposed by Atkins et al (2003) (Rayleigh instability) and Yakovlenko (2004) (induced electrostatic repulsion) but further study is needed. The void formation sequence can be modified by controlling certain external conditions.…”
Section: Bridge Formation During Fiber Fuse Propagationmentioning
confidence: 93%
See 1 more Smart Citation
“…13). This modulation may suggest the instability of the plasma or the surrounding melt as proposed by Atkins et al (2003) (Rayleigh instability) and Yakovlenko (2004) (induced electrostatic repulsion) but further study is needed. The void formation sequence can be modified by controlling certain external conditions.…”
Section: Bridge Formation During Fiber Fuse Propagationmentioning
confidence: 93%
“…Two ideas have been proposed for the driving force behind this void formation. Atkins et al (2003) suggested that Rayleigh instability, or positive surface tension, minimizes the interface area between plasma and molten glass following the analogy of falling water droplets and an air jet in a fluid (see Fig. 11).…”
Section: Microscopic Behaviormentioning
confidence: 99%
“…The fiber fuse phenomenon occurs when input light intensity exceeds about ∼ 2 MW/cm 2 and some external stimuli are applied. [20][21][22][23] It is thought that the creation of a void follows the propagation of a plasmalike disturbance toward the direction of the optical power source at the velocity of the order of 1 m/s; 22 however, the exact mechanism is not fully understood. The appearance of the void formation resembles each other, but in transparent bulk glass, the filament path that reaches the bottom surface needs to be formed to create the periodic void structure as demonstrated above.…”
mentioning
confidence: 99%
“…Therefore, in the near future the fiber fuse phenomenon will pose a real danger to optical communication systems constructed with conventional single-mode fibers [37]. There have already been many experimental and theoretical reports on the fiber fuse phenomenon [20,33,34,36,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. In addition, several devices have been proposed with a view to avoiding the catastrophic damage caused by a fiber fuse, for example, a fiber fuse terminator using a tapered fiber [53] and a thermally-diffused expanded core (TEC) fiber [54] for an input power of not more than 2 W. A device has been reported that can rapidly detect a fiber fuse and terminate it by monitoring the light backreflected from it [55].…”
Section: Applicability To High Power Transmissionmentioning
confidence: 99%